Studi Kajian Interaksionisme Simbolik Pondok Pesantren Misbahulkhoir Bojong Purwakarta - Irfan Pernandi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
EDUCATIONAL COMMUNICATION PATTERN OF SALAFI BOARDING SCHOOL INTERACTIONISM SYMBOLIC STUDY IN MISBAHULKHOIR SALAFI BOARDING SCHOOL BOJONG PURWAKARTA. Salafi boarding school considered as a phenolmena refers to traditional institution of education as an integration of values and culture which contribute to uniqueness tradition and point of view. The uniqueness of salafi boarding school is represented by the symbols and its meaning. The meaning is done by the boarding society, where santri, ustad, and kyai are included, has give us a full meaning of point of view. The meaning as a product of interpretation on symbols to merge in interaction process, and the meaning as the life itself merging in the educational communication pattern of salafi boarding school. The aim of this research are to describe santri, ustad, and kyai understanding on self-concepts, meaning on the symbols as objects, meaning on symbolic activities, and the shared-meaning between members of salafi society. This research is using Herbert Blumer’s Interactionism Symbolic theory with qualitative approach and constructivism method and using Sympathetic Instrospection to analyze. The result of this research is that the self-concept has form the meaning on symbolic objects that include physical and non-physical objects which is forming in symbolic activities so all of it would perform the shared meaning as a educational communication pattern of salafi boarding school.